PENGARUH KOMPRES DINGIN TERHADAP PENGURANGAN NYERI LUKA PERINIUM PADA IBU NIFAS - Mauluddina, Faulia; Veradilla; Reni Saswita; Ria Gustiani (Jurnal Kesehatan dan Pembangunan, 2024)
WHO data (2019) states that the incidence of pereneal rupture in Indonesia is 67.2%, an increase from the previous year, namely 60% in 2019 with an incidence of puerpurium infection of 7%. Factors causing maternal death include postpartum infections. One non-pharmacological technique for treating perineal wound pain is to apply a cold compress. The aim of the research was to determine the effect of cold compresses on reducing perineal wound pain in postpartum mothers. The research method uses a quasi-experimental design, one group pretest and posttest. The population in this study were all postpartum mothers who experienced perineal wounds at BPM Soraya Palembang with a sample size of 30 respondents. The research results showed that the average perineal wound pain in postpartum mothers before being given cold compress therapy was 7.30 and the average perineal wound pain in postpartum mothers after being given cold compresses was 4.63. The statistical test results showed that there was an effect of cold compresses in reducing the pain scale of perineal wounds in postpartum mothers at BPM Soraya Palembang in 2022 with a significant value of 0.000. It is hoped that suggestions from health workers at BPM Soraya Palembang will improve services for postpartum mothers, especially mothers who experience perineal wound pain. Apart from using the pharmacological treatment that has been applied so far, it is hoped that officers can use alternative non-pharmacological treatment such as giving cold compresses.